Joint Development Vector of the Arctic Region in the Framework of National Programs of the Countries of Asia and the Russian Federation - D. G. Popov; D. A. Rogovskoi (Евразийская интеграция: экономика, право, политика, 2019)
The article is devoted to the analysis of Arctic strategies of the countries of Asia and the Russian Federation. The author considers national programs for the development of the Arctic region provided by the Asian countries and the principles on which these programs are built. Much attention is paid to the common features and differences of the strategies under consideration. Arctic strategies are the most important declarations of intentions and opportunities of the countries interested in the region’s development. By exploring and comparing strategies it is possible to predict opportunities for Asian countries — Russian Federation cooperation in the Arctic region. For the research, methods of abstraction, classification, comparative analysis and modeling were used.